Psychological and physical impacts on professional nurses in coping with the COVID-19 pandemic (Research, Society and Development, 2021)
The pandemic caused by COVID-19 caused major changes not only in the organization of health services, but also in terms of the mental and physical health conditions of professionals working on the front lines, especially nurses. Objective: To highlight the main physical and mental implications for nurses in coping with the pandemic by COVID-19. Method: This is an integrative review study with a qualitative approach, using the SCIELO, BDENF and LILACS databases. Results and discussions: The studies highlight the physical and psychological impacts that affect the well-being of nurses working to combat the pandemic, including depression, anxiety, Burnout syndrome, sadness, frustration and among others, arising from nature and current working conditions such as work overload, shortage of personal protective equipment, fear of being contaminated, fear of loss of family members, patients and colleagues, social isolation. Conclusion: Regarding the impact on mental health caused by the pandemic of COVID-19 in the nursing professionals, it highlights the factors that lead to the psychological illness of these professionals and how they are experienced.